Streptococcus sanguinis as an opportunistic bacteria in human oral cavity: Adherence, colonization, and invasion - Pramesti, Hening Tjaturina (Faculty of Dentistry Universitas Padjadjaran, 2016)
Streptococcus sanguinis (formerly S. sanguis) is a Gram-positive, facultative anaerobe, nonmotile , normal inhabitant of the human oral cavity, and a member of the viridans group of streptococci. Among the streptococcus, S. sanguinis is a primary colonizer in the human tooth surface or it is recognize as a ‘pioneer’ by forming dental plaque. The aim of this paper is to review the role of Streptococcus sanguinis in the adherence to and invasion of human tissues. S. sanguinis has been reported that it is associated with healthy tooth surfaces but not with caries. S. sanguinis tend to involved in an interspecies interactions with Streptococcus mutans, which is known as competition/coexistence within dental biofilm. In their colonization, this bacteria used enzyme sortase A (SrtA) to cleave LPXTG-containing proteins sequence and anchored the cell wall, while virulence factors in infective endocarditis involved housekeeping functions such as cell wall synthesis, amino acid and nucleic acid synthesis, and the ability to survive under anaerobic conditions.